Contribuições de um treinamento de habilidades sociais na formação inicial de professores para a Educação Especial - Lessa, Tatiane Cristina Rodrigues (2020)
Educational laws are historical, occupy important spaces and direct pedagogical activities and, consequently, the initial training of teachers. In this context, Special Education becomes a field of visibility since education is a right for all and students of the Special Education target audience are part of these policies and, consequently, of the educational action of future teachers. Countless researches are carried out uniting this public, but in the context of Social Skills Training (THS), there are still few researches involving this population. Thus, this research aimed to develop, implement and evaluate the effectiveness of a Training in Social and Social Educational Skills, with an emphasis on Special Education, for students of undergraduate courses regarding: 1. The repertoire of social, social and educational skills and social attitudes towards inclusion; 2. The perception of the contribution of educational social and social skills to personal and professional training in the view of the participants; 3. Refining the lesson plans of the participants. The research was characterized as experimental, with a pre- and post-test design with a control group and follow-up after the end of four months of intervention. 26 undergraduate students participated in the Pedagogy, Special Education and Degree in Chemistry courses, with only two males and an average age of 21 years. The THS took place at a public university and had 13 intervention sessions, being the data collection instruments: 1. Questionnaire: Knowledge and Use of Educational Social and Social Skills at school, 2. Social Skills Inventory 2, 3. Inventory of Educational Social Skills, 4. Likert Scale of Social Attitudes towards Inclusion, 5. Weekly Meeting Evaluation Form, 6. Social Evaluation Questionnaire for the Program, and 7. Lesson Plans produced by students. For data analysis, repeated measures ANOVA using SPSS, content analysis and textual analysis using the IRAMUEC software were used. The results showed significant differences between the experimental and control groups in the scores of the Social Skills Inventory 2, Social Educational Skills Inventory and Likert Scale of Social Attitudes towards Inclusion, suggesting that the THS was effective for the participants in the experimental group. The content analysis showed that the participants of the experimental group positively evaluated themselves in the participation of the THS and that this type of intervention can help the reflective practice in future teachers. The lesson plans showed no differences in the pre and post-tests, but they did raise important discussions, such as having the student as the main guiding axis in the elaboration of these plans. For future research it is suggested to test how the groups would behave with a long-term HRT (2 semesters for example) maintaining the scientific rigors of control and experimental groups, how the social skills and educational social skills would be (and if they would be) applied by students in the internship contexts encompassing both their own and their supervisors' views, testing how the THS could impact the application of a lesson plan in an internship context and a longitudinal study that understood the entry and exit repertoires of university students who go through such a THS.